The Water Portfolio of the World Bank : Insights from a Review of Fiscal Year 2011 - Scheierling, Susanne M.; Lyon, Kimberly N. (World Bank, Washington, DC, 2015)
This report presents insights from the FY11 review of the World Bank s water portfolio. The report includes a methodological section followed by reviews of four broad areas: the water related commitments managed by the World Bank Group (WBG) for FY011; the water-related commitments of the International Bank for Reconstruction and Development (IBRD) and of the International Development Association (IDA) for FY11; water-related projects approved in FY11; and analytic and advisory activities (AAA), in particular economic and sector work (ESW) and technical assistance (TA), delivered in FY11. The focus of the report is on the new IBRD and IDA commitments in FY11, which are analyzed not only based on data provided in the World Bank s project database but also with data generated by reviewing the Project Appraisal Documents (PADs) using a newly developed questionnaire. Some of the key findings of the FY11 review are the following: Water-related IBRD and IDA commitments comprised about 95% of the overall WBG managed commitments for water. From FY02 to FY11 they grew more than five-fold, from US$1.3 billion to US$7.4 billion largely driven by increased commitments for water supply and sanitation. In FY11 a total of 105 water-related IBRD and IDA projects were approved. Commitments by region were largest for the East Asia and Pacific Region (EAP) and the South Asia Region (SAR) with 30% and 29%, respectively. With regard to the number of projects, Africa was by far the leading Region with 33 projects. Of the 105 water-related projects, only 22% were mapped to the Water Sector Board (WAT) and most of these were water supply and sanitation projects.